Freight transport modeling in emerging countries - Kourounioti, Ioanna; Tavasszy, Lorant A.; Friedrich, Hanno (WCTRS book series., 2021)
"Freight Transport Modeling in Emerging Countries examines freight transport models developed in emerging countries including Turkey, South Africa, India, Chile, and more. It provides a toolbox of successful freight transport model applications, alternative data collection methods, and evaluation techniques for the development of future policies. The book offers solutions for issues related to the urban, national, and international transportation of goods and examines new advances in freight transport models and data collection techniques and their applications in emerging countries. Emerging countries have unique transport-related policies, regulatory structures, logistics systems, and long-term uncertainties that hinder their economic development. This book tackles these issues by examining decision-making models for locating logistics sites such as ports and distribution centers, modeling urban freight movements in megacities and port cities, using existing datasets to get information when data is not available, implementing policies related to the national and international movements of goods, and more. Includes a wide variety of opinions and approaches from subject matter experts around the world Utilizes a case-based approach Includes a range of learning tools that feature chapter openers, end of chapter questions, a glossary, and moreExamines new advances in freight transport models and data collection techniques"--Publisher's description